Calligraffiti on Sarong: The Challenges of Contemporary Batik Creativity in Santri Culture - Taufiqur'anam, Ach. Saidika; Fitriasari, Rr. Paramitha Dyah; Tjahyadi, Sindung (Institut Seni Indonesia Yogyakarta, 2025)
Calligraphy as motifs on sarongs in the santri environment is a challenge because batik motifs with calligraphy are prone to resemble writing that has a sacred meaning and makes the user feel sorry when wearing it. The purpose of this study is to analyze the creative response of contemporary batik artist, Abyan Farazdaq, in creating the motif “calligrafitty”, which is a combination of calligraphy and graffity aesthetics on sarong which is a product of santri culture. The research uses a qualitative approach on Abyan Farazdaq’s batik artwork by collecting data through observation, interviews and visual documentation of artworks. This research show that the artist created a calligraphy pattern, so that the motif cannot be read literally in order to maintain the cultural ethics of sarong users. As a result, the calligraphy motif becomes a form of visual adaptation that maintains the identity of the students and enriches the expression of contemporary batik art. Kaligrafi di Sarung: Tantangan Kreativitas Batik Kontemporer dalam Budaya Santri. Penggunaan motif kaligrafi pada sarung di lingkungan santri menjadi tantangan karena motif batik dengan kaligrafi rentan menyerupai tulisan yang memiliki makna sakral dan membuat penggunanya merasa iba ketika mengenakannya. Tujuan penelitian ini adalah untuk menganalisa respons kreatif seniman batik kontemporer, Abyan Farazdaq, dalam menciptakan motif “kaligrafiti”, yang merupakan kombinasi antara kaligrafi dan estetika graffiti pada sarung yang menjadi produk budaya santri. Penelitian menggunakan pendekatan kualitatif pada karya seni batik Abyan Farazdaq dengan menghimpun data melalui observasi, wawancara, dan dokumentasi visual karya seni. Temuan menunjukkan bahwa seniman menciptakan pola kaligrafiti agar motif tidak terbaca secara literal demi menjaga etika budaya pengguna sarung. Hasilnya, motif Kaligrafiti menjadi bentuk adaptasi visual yang mempertahankan identitas santri serta memperkaya ekspresi seni batik kontemporer.